Determinants of Non-oil Growth in the CFA-Zone Oil Producing Countries : How do they Differ? - Tabova, Alexandra; Baker, Carol (Washington, D.C. : International Monetary Fund, 2011)
Non-oil growth in the CFA oil exporting countries has been lackluster despite their great natural resource wealth. In this paper we study the key determinants of non-oil growth and explore to what extent these countries differ from countries with comparable levels of development that do not depend on nonrenewable resources. Using a panel of 38 countries comprising LICs and CFA zone oil exporters, we find that while real exchange rate appreciation negatively impacted growth in all countries over the period 1985-2008, what distinguishes the oil producers of the CFA zone is the failure of public and private investment to spur non-oil growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet